Lanthanum(III)-Mediated Dearomative Alkylation of Quinolines - Mao, Muzhen; Lou, Wenwen; Guna, Haoer; Chen, Yi-Hung (Synthesis, 2025)
We report the lanthanum(III)-mediated dearomative alkylation of quinoline derivatives that enables direct C2-selective functionalization under mild conditions. This single-step protocol utilizes alkyllithium reagents in the presence of LaCl₃•2LiCl and LiAlH₄ to effect regioselective C–C bond formation while simultaneously reducing the quinoline to afford diverse 2-alkyl-substituted tetrahydroquinolines (THQs). The method displays broad substrate scope, tolerating various alkyl groups and heteroaromatic scaffolds, including acridine and quinoxaline. Mechanistic studies support a stepwise C2-alkylation and C3-hydride delivery pathway. Notably, this strategy allows for rapid access to THQ frameworks prevalent in bioactive natural products and pharmaceutical agents. The use of an lanthanide reagent and mild, scalable conditions highlights the practicality of this transformation. This work establishes a versatile approach to THQ synthesis and expands the repertoire of lanthanide-mediated dearomative functionalization.
Keywords: Quinoline; Lanthanum; alkylation; Dearomatization; Rare earth